Mesosphere and Lower Thermosphere Changes Associated With the 2 July 2019 Total Eclipse in South America Over the Andes Lidar Observatory, Cerro Pachon, Chile. Issue 11 (2nd June 2022) - Vargas, F.; Liu, A.; Swenson, G.; Segura, C.; Vega, P.; Fuentes, J.; Pautet, D.; Taylor, M.; Zhao, Y.; Morton, Y.; Bourne, H.
Abstract: This article presents the results of a week of observations around the 2 July 2019, total Chilean eclipse. The eclipse occurred between 19:22 and 21:46 UTC, with complete sun disc obscuration at 20:38–20:40 UTC (16:38–16:40 LT) over the Andes Lidar Observatory (ALO) at (30.3°S, 70.7°W). Observations were carried out using ALO instrumentation with the goal to observe possible eclipse‐induced effects on the mesosphere and lower thermosphere region (MLT; 75–105 km altitude). To complement our data set, we have also utilized TIMED/SABER temperatures and ionosonde electron density measurements taken at the University of La Serena's Juan Soldado Observatory. Observed events include an unusual fast, bow‐shaped gravity wave structure in airglow images, mesosphere temperature mapper brightness as well as in lidar temperature with 150 km horizontal wavelength 24 min observed period, and vertical wavelength of 25 km. Also, a strong zonal wind shear above 100 km in meteor radar scans as well as the occurrence of a sporadic E layer around 100 km from ionosonde measurements. Finally, variations in temperature and density and the presence of a descending sporadic sodium layer near 98 km were seen in lidar data. We discuss the effects of the eclipse in the MLT, which can shed light on a sparse set of measurements during this type of event. Our results point out several effects of eclipse‐associated changes in the atmosphere below and above but not directly within the MLT. Key Points: Several eclipse‐induced events are observed by mesosphere and lower thermo‐sphere sounders Eclipse‐induced events are not directly generated in the mesosphere and lower thermosphere A spectacular fast, bow‐shaped gravity wave is observed in nightglow images, mesosphere temperature mapper brightness, and lidar temperature, and sodium density